THE EFFECT OF PECTIC SUBSTANCES, HEMICELLULOSE, LIGNIN AND CELLULOSE CONTENT TO THE PERCENTAGE OF BOUND IRON BY DIETARY FIBER MACROMOLECULES: ACIDITY AND LENGTH BOILING TIME VARIATION - Leny Yuanita (Indonesian Journal of Chemistry, 2006)
The aim of the study is to find the effect of dietary fiber components content to the percentage of bound iron by dietary fiber macromolecules at acidity and length of boiling time variation. Yard long bean super green variety as dietary fiber sources. The factorial design was applied at pH 4 and 7 with boiling time of 0 (raw), 5, 15, and 25 minutes; the content of dietary fiber components and percentage bound iron as dependent variables. Two way analysis of variance, least significant difference, and multiple regression analysis were applied. Significance level (α) = 5%.The results of the study reveal that acidity, length of boiling time, and its interaction have effect to the bound iron, but have no effect on pectic substances, hemicellulose and lignin. Decreasing pH and increasing boiling time will increase in cellulose, due to the formation of resistant starch. The content of dietary fiber components has no effect on percentage bound iron; pectic substances and hemicellulose have positif effect, while lignin and cellulose have negatif effect on percentage bound iron.